Spiritual Leadership and Unit Productivity: Does Psychological Need Mediate the Relationship between Spiritual Leadership and Unit Productivity?. (30th November 2022) - Haque, Md Jamirul; Nawaz, Muhammad Zahid; Shaikh, Hamid Ali; Tariq, Muhammad Zubair
Abstract: Under the lens of spiritual leadership and self-determination theories, the current study tested a mediation model that examined the direct and indirect effects of spiritual leadership on work-unit productivity through work-based basic psychological needs (need of autonomy, need of competence, and need of relatedness). Work-based basic psychological needs (WBBPNs) were used as the mediating variables in the study. The data was collected from 317 full-time employees serving in India's service sector and analyzed through AMOS's structural equation modeling. The results revealed that spiritual leadership was a significant predictor of work-unit productivity while work-based basic psychological needs served as partial mediators. The current research added to the literature on spiritual leadership and identified it as a source of intrinsic motivation for the employees. The unique finding of this study enriches the literature on spiritual leadership theory, self-determination theory, work-based basic psychological needs, and work-unit productivity. This study also provided the importance of adopting spiritual leadership in the organization and highlighted the managerial benefits.